AB1029 Ultrasound nail assessment in psoriatic arthritis and psoriasis compared with healthy controls. (15th June 2017) - Janta, I; Rodriguez, O Baniandres; Valor, L; Barrio, J Martinez; Ovalles, JG; Gonzalez, JC Nieto; Gonzalez, C; Longo, J Lopez; Monteagudo, I; Naredo, E
Abstract : Background: Assessment of nail involvement is currently made by clinical assessment using nail psoriasis severity index (NAPSI). Whilst clinical assessment can detect superficial nail changes, the matrix and the extensor tendon region are not accessible for clinical assessment. Musculoskeletal (MS) ultrasound (US) is playing an important role in the evaluation of psoriatic arthritis (PsA) patients. Recently, MSUS has been more used in the evaluation of nail involvement in psoriasis (Pso) and PsA patients. Objectives: The primary objective of this observational, cross-sectional study was to assess the MSUS morphological and vascular abnormalities in nail in PsA and Pso patients compared with healthy controls. The secondary objective was to compare MSUS and clinical assessment of the nail in PsA and Pso patients. Methods: We included patients with PsA (diagnosed according to CASPAR criteria) and patients with Pso without joint involvement (diagnosed by an experienced dermatologist according to clinical findings) and healthy controls. Clinical evaluation consisted in the evaluation of the NAPSI and PASI scores. The MSUS evaluation consisted in the evaluation of 10 hand nails. In B-mode (BM) we evaluated the followings: thickness of the nail bed from the distal phalanx bone surface to the ventral plate (PB) according to Worstman X et al.; thickness of the nail from dorsal to ventral plate (IP); dorsal and ventral plate morphology, echogenicity and integrity. Additionally, we performed a color Doppler (CD) evaluation for the presence of CD signal at the nail bed and matrix level. A score for BM and different scores for CD were calculated for each nail and sums of all nails for BM and CD scores were calculated for each patient. Results: We evaluated 60 patients with PsA, 23 with Pso and 20 controls. 52.4% were female. The mean age (SD; range) was 50.2 (13.6; 23–83). The age was higher in patients (Pso and PsA) than in controls (p<0.001). Patients with PsA were more treated with DMARD (81.7%) while patients with Pso were more treated with topics (73.9%) than DMARDs (13%), (p<0.001). The majority of the patients (96%) had a PASI score less than 12. The NAPSI was higher in Pso patients than in PsA patients (p<0.001); for all controls the NAPSI was 0. US measurements of IP and PB were significantly higher in patients than in controls in the majority of the nail (p<0.045). Total US score for BM was significantly higher in patients than in controls (p<0.001). There were no significant differences for the majority of CD scores between patients and controls. Overall we found weak to moderate positive correlations between NAPSI and US scores for BM, both for matrix and bed. For most of the nails we found no correlation between NAPSI and CDUS scores; for the rest of the nails the correlation was weak, both positive and negative. References: The MSUS measurements and scores showed to be higher in patients with PsA and Pso compared with controls, while CD scores showed no differences. Disclosure of Interest: None declared